Factors Affecting the Development of Community-Based Night Tourism in Vietnam: A Case Study in Sapa-Lao Cai - TRINH THI, Phan; NGUYEN THI PHUONG, Nga; HOANG VAN, Hao (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023, 2023)
This study identifies the factors affecting the development of community-based night tourism, thereby making recommendations to develop community-based night tourism in a sustainable way. Exploratory factor analysis (EFA) combined with linear regression was performed on a survey of 391 tourists who had been to Sapa. Research results show that there are 5 influencing factors: (i) environment, (ii) culture and services, (iii) infrastructure, (iv) security and safety, (v) main tourism development policy. In particular, the factors "security, safety" and "infrastructure" have the strongest influence on the development of community-based night tourism in Sapa. On that basis, the study proposes some recommendations to develop community-based night tourism in a sustainable way .